Social change, suburban lives : an Australian Newtown 1960s to 1990s - Bryson, Lois.; Winter, Ian. (Sydney : Allen and Unwin, 1999)
From federation to the millennium: the historical context of social change. Newtown: the place, the people and the study. Good jobs, not-so-good jobs, no jobs: change and continuity in employment. From decimalisation to deprivation: the growth of income inequality. Homes fit for workers? Family, kin and community.
Keywords: Australia; Social classes; Suburban life; Social classes -- Australia; Suburban life -- Australia; Social change -- Australia; Cost and standard of living -- Australia; Australia -- Politics and government; Australia -- Economic conditions -- Social aspects